GLOBAL TRENDS AND FUTURE PROSPECT OF DEVELOPMENTAL READING: BIBLIOMETRIC ANALYSIS - Khotimah, Husnul; Ismail, Hijril; Rahmaniah, Rima; Humaira, Humaira; Asbah, Asbah (English Review: Journal of English Education, 2025)
The purpose of this research is to present a comprehensive analysis of the literature on developmental reading. The Google Scopus database and Publish or Perish tools were utilized to identify relevant articles. A total of 111 articles, spanning from 2019 to 2024, were reviewed. The references were organized and summarized using Mendeley software. Using the VOSviewer program, the authors analyzed this database and categorized the articles into five groups. Cluster 1 consists of seven items (developmental study, developmental trajectory, difference, fluency, relationship), Cluster 2 includes five items (developmental perspective, developmental trajectory, difference, fluency, relationship), Cluster 3 comprises four items (Chinese child, dyslexia, training, word), Cluster 4 contains three items (adult, developmental disability, intellectual), and Cluster 5 encompasses three items (developmental relation, evidence, reading comprehension).